Food Sellers Strategy Based on Customer Reviews Before and During Covid-19 Pandemic in Indonesia - Saraswati, Immaculata Diana; Suharyanti, Yosephine; Daryanto, Yosef (Industrial Engineering, Faculty of Engineering, Universitas Sebelas Maret, 2022)
The survival and resilience of food sellers in Indonesia during the Covid-19 pandemic is important to be discussed. This study proposes new strategies for food sellers in Indonesia based on customer reviews before and during the pandemic, and food sellers' competition profile. Customer reviews are scraped from 20 food sellers in Java, Indonesia. A text mining is then applied, and the texts collected are classified into 11 attributes. The next process is sentiment analysis to separate the positive and the negative reviews, to be analyzed further in two types of gap analyses. The first is gap analysis between positive and negative reviews to portray the food sellers’ strengths and weaknesses. The second gap analysis identifies the gap of customer reviews before and during the pandemic to predict the change of customers’ needs. The results show that product, place, and services are always the customer’s top-of-mind attributes, no matter in normal or pandemic situations, so that food seller should always maintain those aspects. This study also identifies several new strategies related to the health protocols. Regarding to online business competition, this study observes the food sellers’ growth in online marketplace. The result shows that the growth score of food sellers increases significantly from 2 to 9 per month because of the pandemic. Thus, food sellers need to consider the opportunity for online business, while maintaining their strengths. Compared to similar studies in other countries, the findings of this study differ in terms of the dominant attributes, related to different cultures.